1980
DOI: 10.1007/bf00310436
|View full text |Cite
|
Sign up to set email alerts
|

The antidote effect of thiosulphate and hydroxocobalamin in formation of nitroprusside intoxication of rabbits

Abstract: Sodium nitroprusside (SNP) and hydroxocobalamin (HC) - in molar ratios of 1:4, 1:5, and 1:8, respectively - were infused simultaneously during 4 h into two veins of separate ears of conscious rabbits. Controls received HC only. Sodium thiosulphate (ST) was infused with SNP at molar ratios of 1:4, 1:5, and 1:10. The observation period was 48 h. With the lowest dose of HC (1:4), SNP produced a severe metabolic acidosis; three of ten animals died during the infusion, an additional six within 24 h. When the 1:5 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Following vitamin B12 (hydroxocobalamin) intraperitoneal administration (70 mg kg À1 day À1 ) for a 21-day period to rats, investigators observed significant increases in the examined tissue concentrations of cobalt in the diaphragm and myocardium (other organs were not examined) (Pery-Man et al 1996), and no significant adverse histological effects of vitamin B12 administration was observed in the tissues examined. In contrast, investigators observed that intravenous administration of a single several-hundred milligramper-kilogram dose of vitamin B12 (hydroxocobalamin) to rabbits produced significant acute histological changes to organs, including the kidney, liver, and heart (Hobel et al 1980). Importantly, since neither of these two studies attempted to study the potential adverse histological effects of chronic long-term low doses of vitamin B12 in organs such as the brain, one cannot make any concrete extrapolation from the results reported in these animal studies to the injection of methylcobalamin into humans.…”
Section: Discussionmentioning
confidence: 87%
“…Following vitamin B12 (hydroxocobalamin) intraperitoneal administration (70 mg kg À1 day À1 ) for a 21-day period to rats, investigators observed significant increases in the examined tissue concentrations of cobalt in the diaphragm and myocardium (other organs were not examined) (Pery-Man et al 1996), and no significant adverse histological effects of vitamin B12 administration was observed in the tissues examined. In contrast, investigators observed that intravenous administration of a single several-hundred milligramper-kilogram dose of vitamin B12 (hydroxocobalamin) to rabbits produced significant acute histological changes to organs, including the kidney, liver, and heart (Hobel et al 1980). Importantly, since neither of these two studies attempted to study the potential adverse histological effects of chronic long-term low doses of vitamin B12 in organs such as the brain, one cannot make any concrete extrapolation from the results reported in these animal studies to the injection of methylcobalamin into humans.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, these substances also interfere with iodine uptake by disrupting metabolism of thyroid and vitamin B12 [49]. In this context, Hobel et al evaluated the antidote effect of hydroxocobalamin and thio-sulphate after infusing sodium nitroprusside into the rabbits [50].…”
Section: Historical and Clinical Aspects Of Sodium Nitroprussidementioning
confidence: 99%